Students' Motivations in Learning English Based on Gender Difference System in Grade 7 MTsN 12 Tanah Datar - Welli Amelia Amelia; Ainul Addinna (Universitas Negeri Padang, 2023)
This study aimed to make an analysis of students motivation based on gender difference system at the first grade of stdents MTsN 12 Tanah Datar. This study used a quantitative method to collect data and was a descriptive study with 40 statements on a Likert scale with four scales: 1 (tidak setuju), 2 (kurang setuju), 3 (setuju), and 4 (sangat setuju). The statements were divided into two categories: achievement motivation and competence motivation. A total of 35 female students and 24 male students from Grade seven MTsN 12 Tanah Datar composed the study's sample. Item validity, namely the product moment, is used in the validity test. Cronbach's alpha was used to test the instrument's reliability.The descriptive method of data analysis was presented as a percentage. The findings showed that students had a high motivation for learning English. In particular, the positivity of the statements for the sake of achievement motivation (10 statements) was above the mean total for female (3,89%) and for male (3,71%), the positivity of the statements for the sake of competence of motivation (10 statements) was above the mean total for female (3.89%) and for male (3.72%). As the result student’s motivation based on gender difference system was seen high motivation for learning English.